Influence of external funders on social enterprise business models: a causation-effectuation exploratory study - Njenge, Yandisa Lusapho (University of the Witwatersrand, Johannesburg, 2021)
Social entrepreneurship research is a growing research field, growth that can also be seen in the practice of social entrepreneurship. Dominant literature in the field focuses on the definition of social entrepreneurship and the traits of the social entrepreneur and does not look deeply at social entrepreneurship practices and interactions with other institutions. To address these shortcomings in research, this study systematically analyses the dominant definitions of social entrepreneurship and proposes an all-encompassing definition. The study also focuses on the interaction between social enterprises and external funders, exploring how social enterprises implement business models and the influence that external funders have on the business model implementation. A qualitative study was used to answer the research questions by exploring the business model implementation in ten case studies. A total of 26 respondents were interviewed as founding social entrepreneurs, internal staff members or external funders. The study relied on theoretical propositions from the literature review to analyse the data inductively and this process resulted in within-case themes. Further analysis of the within-case themes resulted in five cross-case themes. What was of interest was how operating in a resource-constrained environment impacts business model implementation. The ten case studies interviewed displayed structured or causal mechanisms in implementing their business models, which differs from the view that social entrepreneurs are effectual in behaviour. A theoretical framework with five propositions is put forward by this study. The theoretical framework propositions are: Social enterprises operate in resource-constrained environments and rely on external funding from inception. Social enterprises in resource-constrained environments approach external funders that do not expect a financial return. Social enterprises in resource-constrained environments implement business model dimensions that will lead to the achievement of the social mission. Externally funded social enterprises implement their business models in a causal manner. External funders not expecting financial returns apply limited influence on the business models of the social enterprises they fund. In accordance with the findings of this study, some suggestions for future research are put forward.
A Thesis submitted in fulfilment of the requirements for the Doctor of Philosophy Degree in the Wits Graduate School of Business, Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg. 2021
Keywords: Social enterprise; Social entrepreneur; Social entrepreneurship; Business model; Resource constrained environment; External funding; Causation; Effectuation; SDG-17: Partnerships for the goals